Disruption avoidance by stabilizing coupled MHD modes using resonant magnetic perturbations on J-TEXT. (1st March 2023) - He, Ying; Wang, Nengchao; Ding, Yonghua; Li, Da; Zhou, Song; Mao, Feiyue; Shen, Chengshuo; Jia, Ruo; Ren, Zhengkang; Gao, Yuan; Zhang, Zhichao; Li, Shuhao; et al.
Abstract: The coupling of multiple magnetohydrodynamic (MHD) modes can lead to mode locking and major disruption in tokamak plasmas. In the J-TEXT tokamak, the coupling between two small modes, i.e. m / n = 2/1 and 3/1 modes ( m and n are poloidal and toroidal mode numbers, respectively), appears when the edge safety factor is reduced to the vicinity of 3. After the mode coupling, the toroidal phase difference between the 2/1 and 3/1 modes equals 0 in the low field side midplane. This phase relation of coupled modes leads to mutual destabilization and even major disruption. A control scheme to avoid disruption caused by coupled modes by resonant magnetic perturbations (RMPs) is presented. It is found that the application of RMP significantly changes the evolution of the coupled modes. The coupling of the 2/1 and 3/1 modes occurs earlier as the RMP amplitude increases. The RMP with moderate amplitude can suppress the growth of 2/1 and 3/1 coupled modes and hence avoid disruption. These results provide a possible strategy for the suppression of neoclassical tearing mode (NTM) seed islands on International Thermonuclear Experimental Reactor (ITER) or future fusion reactors.